Cerium substitution in LaCoO3 perovskite oxide as bifunctional electrocatalysts for hydrogen and oxygen evolution reactions. Issue 22 (1st June 2021) - Ji, Dingwei; Liu, Changhai; Yao, Yanhua; Luo, Linlin; Wang, Wenchang; Chen, Zhidong
Abstract : We proposed a facile fabrication of Ce-doped LaCoO3 perovskite oxide for highly efficient application in both HER and OER. Abstract : Perovskite oxides have attracted great attention in electrochemistry due to their compositional and structural flexibility. Herein, microwave/ultrasound assisted hydrothermal procedures were developed to synthesize Ce-doped LaCoO3 perovskite oxide as bifunctional electrocatalysts for OER and HER application, achieving highly efficient bifunctional catalytic performance. The obtained LCC4 exhibited excellent electrocatalytic activity with an overpotential of 380 mV and 305 mV at 10 mA cm −2 toward OER and HER, respectively. The lower Tafel slopes of 80 mV per decade and 144 mV per decade for OER and HER, respectively, indicated the faster reaction kinetics for the improved inherent electrocatalytic activity. The outstanding long-term durability of LCC4 in alkaline conditions was also vital to the practical applications of water electrolysis. The improved bifunctional electrocatalytic activity was attributed to the synergistic effects of excellent conductivity and enriched active sites arising from A-site substitution. This work not only provides an efficient strategy for the development of perovskite oxide-based electrocatalysts but also puts forward a new insight on bifunctional electrocatalysts for overall water splitting.